2019
DOI: 10.1155/2019/7498518
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Acid Soil Management for Growth, Nodulation, and Nutrient Uptake of Faba Bean (Vicia faba L.) in Lay Gayint District, Northwestern Highlands of Ethiopia

Abstract: Soil acidity is one of the forms of soil degradation affecting sustainable crop production adversely in the Ethiopian highlands. In order to contribute to soil acidity amelioration and crop productivity improvement on acid soils, an experiment was conducted to investigate the effects of lime, mineral P, FYM, compost, and rhizobium on growth, nodulation, and nutrient uptake of faba bean (Vicia faba L.) in cultivated acid soil under greenhouse conditions. Twenty treatments were tested in isolations as well as su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Predominantly acid-affected southern, northwestern, southwestern, and central parts of Ethiopia (Mosissa, 2018) are characterized by high rainfall (majority above 1400 mm) associated with inherently acidic soils such as Nitisols, Alisols, and Fluvisols (Agegnehu et al, 2019;Kidanemariam, 2013). Locations such as Nedjo, Diga, Gimibi, Bedi (in the west); Chencha, Sodo, Hagerselam, Endibir (in the south), and Awi, Gozamin, and Senan (in the northwest) have been known for problems linked to acidity (Fekadu et al, 2019;Haile & Boke, 2011;MoARD, 2007). The fact that most of these predominantly acidic areas are found in high production zones results in significant losses in production, and the choice of crops is also restricted to acid-tolerant crop species and varieties (Abate et al, 2013(Abate et al, , 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Predominantly acid-affected southern, northwestern, southwestern, and central parts of Ethiopia (Mosissa, 2018) are characterized by high rainfall (majority above 1400 mm) associated with inherently acidic soils such as Nitisols, Alisols, and Fluvisols (Agegnehu et al, 2019;Kidanemariam, 2013). Locations such as Nedjo, Diga, Gimibi, Bedi (in the west); Chencha, Sodo, Hagerselam, Endibir (in the south), and Awi, Gozamin, and Senan (in the northwest) have been known for problems linked to acidity (Fekadu et al, 2019;Haile & Boke, 2011;MoARD, 2007). The fact that most of these predominantly acidic areas are found in high production zones results in significant losses in production, and the choice of crops is also restricted to acid-tolerant crop species and varieties (Abate et al, 2013(Abate et al, , 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Gomaa et al (2002) reported positive effects of using certain bioorganic applications on growth and yield of Vicia sativa. In this context, Fekadu et al (2019) and Elnesairi and Elssalem (2020) indicated that the use of organic and inorganic amendments improves faba bean growth. On the other hand, Mahmoud et al (2004) observed that the use of organic manures at rates 4.8-7.1-t ha -1 enhanced faba bean growth.…”
Section: Discussionmentioning
confidence: 99%